FRANCHISING AND ITS APPLICATIONS IN SLOVAK REPUBLIC - MIRIAM JANKALOVÁ; RADOSLAV JANKAL (Annals of the University of Petrosani: Economics)
The paper focus on characteristic of franchising as the opportunity for firms to start the business. Franchising is an agreement in which franchisees receive the right to operate a business under the franchisor’s trade name in exchange for paying a fee and operating according to a specific plan (Flităr, 2003). In other words, this method of distribution is based on a contract in which the franchisor gives franchisees the right to operate a business under its trade name. In exchange, the franchisees pay a specific amount and operate the business according to a plan specified by the franchisor (Flităr, 2003). We also analyse the situation in Slovak republic where franchising is still used not so often as in the other EU countries.